ELECTROPHYSIOLOGICAL FINDINGS AND OUTCOME OF PATIENTS WITH IDIOPATHIC LEFT VENTRICULAR TACHYCARDIA - Iftekhar, Faisal Malik; Hussain, Chiragh; Khan, Imran; Sami, Abdul; Awan, Zahid Aslam (Journal of Postgraduate Medical Institute, 2021)
ABSTRACT: Objective: To find out electrophysiological findings and outcome of radiofrequency ablation of Idiopathic left ventricular tachycardia. Methodology: This retrospective study was conducted in the Cardiac Electrophysiology department of Hayatabad Medical Complex, Peshawar. Data was collected from records of the patients presented with ILVT from January 2007 to January 2018. Seventy five patients of both genders and any age, who were vitally stable, were included. Only patients who successfully fulfilled the Zippes Triad criteria for idiopathic left ventricular tachycardia (ILVT) had been labeled as cases of ILVT after and electrophysiology studies and radiofrequency ablation were carried out for such patients. During ablation, diastolic potential was main target of ablation. Data was entered in SPSS version 18 and analyzed for descriptive statistics. Results: Out of 75 patients, 63 were males and 12 were females. Ninety six percent of the patients complained of palpitations and 60% of the patients complained of chest pain accompanied by palpitations. Right bundle branch block with left axis deviation was the most common ECG finding whereas RBBB with right axis deviation was found in 2.6% patients. All ablations were successful, i.e. a success rate of 100% with recurrence occurring in only 6.6% cases. Apart from one, all the ablations were done with retrograde technique. Conclusion: ILVTs are common arrhythmias in our population and catheter ablation is the standard and effective treatment.